A General Review on Women Empowerment in Nepal - Acharya, Sharmila (NUTA Journal, 2023)
In developing nations like Nepal, gender equality and women empowerment are always burning issues. Most of the indicators of women empowerment in Nepal are found below the standard. Thus the study, tries to explore the condition of women at home and their socioeconomic challenges. Many studies in the present era, in the issues of causes of gender inequality and remedies for women empowerment are the need of the modern world including Nepal. The study is the general review of available resources in internet about the issues (need and solution) of women empowerment of Nepal. The study analyses the inequality of women and its solution in Nepalese society. The study concludes, that the review identifies, inequality between men and women, domestic violence, sexual harassment, and illiteracy are the major problems. In conclusion, the opportunity for education, health, job and entrepreneurship access are the basic tools of women empowerment to mainstream gender inequality in Nepal.